2017
DOI: 10.15171/ijhpm.2017.117
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Influence Enrolment and Retention in Ghana’ National Health Insurance Scheme

Abstract: Background: The government of Ghana introduced the National Health Insurance Scheme (NHIS) in 2004 with the goal of achieving universal coverage within 5 years. Evidence, however, shows that expanding NHIS coverage and especially retaining members have remained a challenge. A multilevel perspective was employed as a conceptual framework and methodological tool to examine why enrolment and retention in the NHIS remains low. Methods: A household survey was conducted after 20 months educational and promotional a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
115
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(133 citation statements)
references
References 30 publications
16
115
2
Order By: Relevance
“…Satisfaction scores with the other accessed areas were mixed: with uninsured patients expressing higher satisfaction levels with hospital accessibility, doctor's consultation, nursing care and quality of care; while NHIS enrollees expressed higher satisfaction scores with laboratory services, patient waiting time and cost of care, all without statistical significance. These findings suggest that patients generally experience varying levels of healthcare quality, which is comparable to the result of some previous studies [16][17][18] and recommends that efforts towards quality improvement and sustainable delivery of excellent health services should not be targeted towards a particular group but to all the patients.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Satisfaction scores with the other accessed areas were mixed: with uninsured patients expressing higher satisfaction levels with hospital accessibility, doctor's consultation, nursing care and quality of care; while NHIS enrollees expressed higher satisfaction scores with laboratory services, patient waiting time and cost of care, all without statistical significance. These findings suggest that patients generally experience varying levels of healthcare quality, which is comparable to the result of some previous studies [16][17][18] and recommends that efforts towards quality improvement and sustainable delivery of excellent health services should not be targeted towards a particular group but to all the patients.…”
Section: Discussionsupporting
confidence: 84%
“…Bauchet, et al [14] in India reported that insurance status has no influence on the quality of care received by patients. Abuosi, et al in Ghana reported that overall, there was no significant difference in perceptions of quality between insured and uninsured patients [15], while some other studies in Ghana and Haiti reported that patients (insured and uninsured) experience poor quality of care and it can deter healthcare utilization as well as affect health insurance schemes negatively by discouraging enrolment and renewal [16][17][18].…”
Section: Introductionmentioning
confidence: 97%
“…Improving the assessment of the fairness of basic medical insurance would help provide reliable support for system optimization. However, in the evaluation of the institutional effect, it remains necessary to define fairness clearly and draw on the literature and main influencing factors that cause inequitable benefits of the group's basic medical insurance, including, for example, objective factors, such as individual health and age and the differences in social factors, such as risk, income, and education [17][18][19][20]; among them, the social factors are the main cause of social inequality. Therefore, the definition of fairness in this paper emphasizes the differences between income groups in basic medical insurance, that is, different income groups are not provided with the same health rights despite being provided the same health insurance.…”
Section: Introductionmentioning
confidence: 99%
“…Achieving fairness in basic medical services is a basic task in the reform of the medical and health systems in countries worldwide and has received increasing attention from the academic world. Scholars have studied the differences in the fairness of the basic medical insurance systems in typical countries and regions, such as the perspective of the relationship between national income and health inequality in different countries (or regions) [20]; the benefit of the difference between income groups was studied from the perspective of basic health service use and medical insurance compensation level [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Substantial socioeconomic inequalities remain in NHIS enrollment, with fewer low‐income and informal sector households participating in the scheme . Previous studies have identified a wide range of factors that may be responsible for the inequities in coverage, including poverty, lack of information, poor quality of care, unaffordable premiums, and administrative bottlenecks . Most of Ghana's population work in the informal sector and are reliant of informal support arrangements to the meet their daily needs, including health care.…”
Section: Introductionmentioning
confidence: 99%